"I wouldn't even sit on one." Relevant attitudes towards tricycles for adults. (May 2018) - Hagemeister, Carmen; Krause, Julia; Bunte, Heike
Highlights: Practical aspects are irrelevant for the decision to try a tricycle or not. Perceived safety is irrelevant for this decision. Persons who associate tricycles with disability or seniors are less willing to go on a trial ride. It is central if a potential trial rider sees a tricycle as fitting into the personal lifestyle. Abstract: Tricycles could help to improve the traffic safety of cyclists as they make it easier to deal with bad surfaces. They are an option to ensure independent mobility for persons who cannot ride a bicycle. But on roads tricycles are rare. Compared to bikes, trikes are considered to have substantial disadvantages. In this study, differences between persons who can imagine going on a trial ride with a trike and persons who cannot imagine going on a trial ride are assessed. In effect, practical differences between bikes and trikes are unimportant, as is safety perception. What is important is how far a trike is associated with age and disability, how well it fits to the individual's lifestyle and whether it is seen as sporty. For the marketing of trikes, safety arguments are irrelevant; references to a "senior" product could be counterproductive.